2020
DOI: 10.1111/jvec.12398
|View full text |Cite
|
Sign up to set email alerts
|

Response of small mammal and tick communities to a catastrophic wildfire and implications for tick‐borne pathogens

Abstract: Through their potentially devastating impacts on the environment, wildfires may impact pathogen, vector, and host interactions, leading to changing risks of vector‐borne disease in humans and other animals. Despite established risks for tick‐borne disease and increasing frequency and severity of wildfires in the United States, impacts of wildfire on ticks and tick‐borne pathogens are understudied. In 2015, the large Wragg fire extensively burned a long‐term field site at Stebbins Cold Canyon University of Cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…Interestingly, the study found a significant shift in tick genera proportions from predominantly Ixodes spp to more equal proportions of Ixodes and Dermacentor spp at both sites pre- and post-fire: at the Cold Canyon burned site, 100% of the ticks pre-fire were of the Ixodes genus, which shifted to 55.81% Ixodes and 44.19% Dermacentor post-fire; at the Quail Ridge unburned site, 87.5% of the ticks pre-fire were of the Ixodes genus and 12.5% were of the Dermacentor genus, which shifted to 31.25% Ixodes and 68.75% Dermacentor post-fire. 101 The authors also found a significant increase in the number of animals infested with ticks at both sites when considered together, which was primarily driven by an increase at the unburned Quail Ridge site from 9.9% pre-fire to 48% post-fire. 101 Additionally, a longer duration of infestation was seen at the unburned site where animals were only infested during the Spring and Summer pre-fire but through all four seasons post-fire.…”
Section: Insect Vectorsmentioning
confidence: 88%
See 4 more Smart Citations
“…Interestingly, the study found a significant shift in tick genera proportions from predominantly Ixodes spp to more equal proportions of Ixodes and Dermacentor spp at both sites pre- and post-fire: at the Cold Canyon burned site, 100% of the ticks pre-fire were of the Ixodes genus, which shifted to 55.81% Ixodes and 44.19% Dermacentor post-fire; at the Quail Ridge unburned site, 87.5% of the ticks pre-fire were of the Ixodes genus and 12.5% were of the Dermacentor genus, which shifted to 31.25% Ixodes and 68.75% Dermacentor post-fire. 101 The authors also found a significant increase in the number of animals infested with ticks at both sites when considered together, which was primarily driven by an increase at the unburned Quail Ridge site from 9.9% pre-fire to 48% post-fire. 101 Additionally, a longer duration of infestation was seen at the unburned site where animals were only infested during the Spring and Summer pre-fire but through all four seasons post-fire.…”
Section: Insect Vectorsmentioning
confidence: 88%
“… 101 The authors also found a significant increase in the number of animals infested with ticks at both sites when considered together, which was primarily driven by an increase at the unburned Quail Ridge site from 9.9% pre-fire to 48% post-fire. 101 Additionally, a longer duration of infestation was seen at the unburned site where animals were only infested during the Spring and Summer pre-fire but through all four seasons post-fire. 101 The number of small mammal species more than tripled from pre- to post-fire at the burned site, while near doubling from pre- to post-fire at the unburned site.…”
Section: Insect Vectorsmentioning
confidence: 88%
See 3 more Smart Citations